2019
DOI: 10.1051/e3sconf/201913501052
|View full text |Cite
|
Sign up to set email alerts
|

Phenatrene biodestructors isolated from soils of large cities

Abstract: The article shows the possibility of bacterial degradation of crystalline phenanthrene in its pure form. The results make it possible to create a technology for processing chemical industry waste in the form of “as is” without dilution with neutral substrates or clean soils. Bacteria Pseudomonas sp., Completely destroying crystals moistened with a solution of salts of Raymond’s medium, were isolated from a soil sample taken in Soho Square, London (UK). Similar destructors, but with less activity, were isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In practical terms, this will make it possible to reduce the volume of microbiological manipulations when analyzing soil samples for the presence of destructors of organic pollutants by taking and studying the most promising samples, since, as a rule, isolated crops have a very ordinary activity. Nevertheless, urban soils of megalopolises with a long industrial history can be a source of destructors of organic pollutants, which are not inferior in their activity to crops isolated from toxic waste accumulators [3]. To test this assumption, we selected relatively ecologically clean and highly polluted locations where indicator plants are in the closest possible growing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In practical terms, this will make it possible to reduce the volume of microbiological manipulations when analyzing soil samples for the presence of destructors of organic pollutants by taking and studying the most promising samples, since, as a rule, isolated crops have a very ordinary activity. Nevertheless, urban soils of megalopolises with a long industrial history can be a source of destructors of organic pollutants, which are not inferior in their activity to crops isolated from toxic waste accumulators [3]. To test this assumption, we selected relatively ecologically clean and highly polluted locations where indicator plants are in the closest possible growing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…A comparative proteomic analysis of three different strains led to the identification of 13 proteins associated with resistance to bile acids. [37]. In addition, a change in the genes associated with cell surface proteins and metabolism suggests that.…”
Section: Analysis Of Probiotic-assosiated Genes Of Lactobacillusmentioning
confidence: 99%
“…Firstly, Word of Mouth Strategy: organizations in air transport should maintain their reputation by offering e-service as what was promised to passenger on price, features, and etc [24,25]. Training is another tool to focus since the finding confirmed that word of mouth has become the most important factor contributing to customer loyalty which is a vital tool in air transport.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%